1986
DOI: 10.1139/z86-130
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for displacement of a North American spider, Steatoda borealis (Hentz), by the European species S. bipunctata (Linnaeus) (Araneae: Theridiidae)

Abstract: The European spider Steatoda bipunctata has apparently been introduced into North America through human transport. The earliest American collections were made in Nova Scotia in 1913. Until about 1933, specimens were known only on the coast of the Atlantic provinces, Maine, and along the St. Lawrence River and Lake Ontario, but they are now found widely in the Atlantic Provinces, northernmost New England, and southern Québec and Ontario. Habitats include buildings, bridges, piles of lumber and firewood, and cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…Alternatively, Brown (1981) concluded there was inferential evidence of interspecific competition among orb weavers and Spiller (1984) found interspecific competition between spiders was significant and appeared to play an important role in structuring their community. Nyffeler et al (1986), in a study similar to the present one, concluded that competition was occurring between Steatoda bipunctata (Linnaeus) a European immigrant into North America, and S.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Alternatively, Brown (1981) concluded there was inferential evidence of interspecific competition among orb weavers and Spiller (1984) found interspecific competition between spiders was significant and appeared to play an important role in structuring their community. Nyffeler et al (1986), in a study similar to the present one, concluded that competition was occurring between Steatoda bipunctata (Linnaeus) a European immigrant into North America, and S.…”
supporting
confidence: 77%
“…The two species are the same size, show a high level of microhabitat and diel activity overlap, and both select the same prey species at the same rate (Nyffeler et al 1986). Although Nyffeler et al (1986) felt that displacement was occurring they were unable to identify the mechanism by which it was operating. S.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other evidence for competition comes from cases of geographical displacement of a local species by an immigrant (Nyffeler et al, 1986), and of character displacement in sympatry (Toft, 1980). Competition by both interference and exploitation was found between some Araneidae species (Spiller, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The negative impacts of invasive ant species, for example, have been enormous (Holway et al 2002). As generalist arthropod predators, spiders have the potential to affect native arthropod species; nevertheless, spiders have been largely overlooked as invasive species (but see Nyffeler et al 1986;Hann 1990;Burger et al 2001;Gruner 2005). Once established, invasive spiders may be viewed as either beneficial arthropods in agroecosystems, or as disruptive predators in native ecosystems.…”
Section: Introductionmentioning
confidence: 99%